2010
DOI: 10.2353/ajpath.2010.090058
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Up-Regulation and Activation in Dysferlin-Deficient Skeletal Muscle

Abstract: A deficiency of the dysferlin protein results in limb girdle muscular dystrophy type 2B and Miyoshi myopathy, with resulting plasma membrane abnormalities in myofibers. Many patients show muscle inflammation, but the molecular mechanisms that initiate and perpetuate this inflammation are not well understood. We previously showed abnormal activation of macrophages and hypothesized that activation of the inflammasome pathway may play a role in disease progression. To test this, we studied the inflammasome molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(185 citation statements)
references
References 36 publications
11
162
1
2
Order By: Relevance
“…It is enigmatic that dysferlinopathy triggers a prominent inflammatory response, but recent findings have revealed some potential causes. Dysferlindeficient monocytes from SJL/J mice were reported to have increased phagocytic activity (26), and dysferlin deficiency induces an upregulation of inflammasome (27). However, a more recent study (18) did not find a difference in phagocytic activity of dysferlindeficient monocytes using C57BL/10-SJL.Dysf mice, which have a more controlled genetic background.…”
Section: Introductionmentioning
confidence: 85%
“…It is enigmatic that dysferlinopathy triggers a prominent inflammatory response, but recent findings have revealed some potential causes. Dysferlindeficient monocytes from SJL/J mice were reported to have increased phagocytic activity (26), and dysferlin deficiency induces an upregulation of inflammasome (27). However, a more recent study (18) did not find a difference in phagocytic activity of dysferlindeficient monocytes using C57BL/10-SJL.Dysf mice, which have a more controlled genetic background.…”
Section: Introductionmentioning
confidence: 85%
“…For example, inflammasomemediated IL-1b overproduction is involved in the pathogenesis of type 2 diabetes, liver damage and muscular dystrophy. [132][133][134] Inflammasome-mediated processes were also observed in cancer, but the association between the inflammasome/IL-1b axis and cancer development is ambiguous. In some studies the inflammasome seems to promote inflammation-mediated tumor development, also confirmed in lung mesotheliomas caused by silica and asbestos.…”
Section: Adaptive Immunity-mediated Diseasesmentioning
confidence: 99%
“…Dysferlinopathies are associated with increased myofiber necrosis and enhanced immune and inflammatory responses, gauged by increased monocyte and macrophage infiltration (28,29). Previously, we reported that impaired recovery of contractile torque following large-strain injury (LSI) in dysferlin-null mice was concurrent with an increase in necrosis and macrophage infiltration (19).…”
Section: Significancementioning
confidence: 99%